HIV-Polymyositis progressing to inclusion body myositis: clues to earlier diagnosis - Basant, Rai Bhuvaneshlal (Department of Medicine, 2025)
Inflammatory myopathies in Human Immunodeficiency Virus (HIV)-positive patients may include polymyositis (PM), dermatomyositis and inclusion body myositis (IBM). Although PM is still mentioned, it is thought to be rare since the discovery of myositis autoantibodies. In the last few years it has been reported that several cases who were initially diagnosed as HIV-associated PM (HIV-PM) clinically and on muscle biopsy, change into a treatment-resistant HIV-IBM clinical phenotype. These cases are referred to as HIV-PM/IBM overlap syndrome. In recent years at Groote Schuur Hospital (GSH), we have also encountered patients with HIV-PM/IBM. Aims The aims of our study were: (1) to describe the demographic, clinical and laboratory findings in patients that were being treated for refractory “PM” and in whom the clinical diagnosis was changed from HIV-PM to HIV-IBM at the neurology unit, Groote Schuur Hospital (GSH) (2) to identify the earliest clues for this progression from HIV-PM to HIV-IBM. Methods A retrospective folder review was conducted for nine patients with HIV-IBM who interacted with the neurology service at GSH from 1 January 2000 to 30 November 2023. The duration between the diagnosis of PM and when they first satisfied the diagnostic criteria of IBM by their case notes were recorded. Results All the patients were female with a median age of 50 years at IBM diagnosis. Proximal lower limb weakness was the initial complaint of all of our patients with median age of 36 years. The median maximum CK recorded was 2500 IU/L. None of the patients had a recorded CK of more than 15 times the upper limit of normal. The median interval between symptom onset to IBM diagnosis was 11 years (range: 6-15) and the median interval between PM diagnosis and IBM diagnosis was 9 years (range: 3-14). Patients were examined after a median symptom duration of 12 years. After approximately 1.5 years of follow up, two of six patients already satisfied the ENMC 2011 clinical criteria for IBM. Of the most severely affected muscles in the lower limbs with Medical Research Council (MRC) muscle power grades of 0-2 (out of 5), the knee extensors were most frequent (≥ 90% of cases). In the upper limbs, the finger flexors were the most involved with moderately weak muscles in 50% of cases. Four (44.4 %) patients reported mild dysphagia at IBM diagnosis visit. Seven of nine patients received immunotherapy. All patients who received any form of immunosuppressive therapy received prednisone (median duration: 137 months [(range: 24-180)]). The median number of immunosuppressants used by patients who received any form of immunotherapy (n=7) was four. All nine patients had muscle biopsies between 12 and 35 months after onset of symptoms. The most important findings were that all patients had evidence of inflammatory infiltrates. An increase in MHC 1 expression and mitochondrial abnormalities (i.e COX – /SDH + fibres) were noted in all four patients in whom immunohistochemical staining and combined SDH and COX staining were performed. At the visit to neurology, five patients could be categorized as clinically defined IBM and four were defined as clinically probable IBM. Conclusions Earlier recognition of this progression from HIV-PM to HIV-IBM was not possible due to poor awareness of this entity. Three of our HIV-IBM patients were younger than the age criteria for non-HIV sporadic IBM at the IBM visit. As all these patients had otherwise typical IBM features but were younger, the age criteria of ENMC 2011 may not be applicable to HIV-IBM patients. Only four patients subjectively and objectively responded to immunosuppressive treatment for a short median period of 22 months (range: 8-53). Drug refractoriness should alert the clinicians of this clinical progression from HIV-PM to HIV-IBM. A relatively high CK but less than 15 times the upper limit of normal is another clue for this clinical entity. In this study all the patients who had COX/SDH staining showed marked COX negative and SDH positive fibres and hence this test should be performed in all inflammatory myopathy muscle biopsy samples for earlier recognition of HIV-IBM.